Mid Regional Natriuretic Peptide for Predicting Prognosis of Hypertrophic Cardiomyopathy (Academia Journal of Medicine, 2020)
Background: Hypertrophic cardiomyopathy (HCM) is a genetic disorder of cardiac myocytes that is characterized by cardiac hypertrophy, cel lular disarray and interstitial fibrosis. Mutation of MYH7 and MYBPC3 encoding proteins β-myosin heavy chain and myosin binding protein C, respectively, are the two most common genes involved, together accounting for about 50% of cases. The present study was conducted to evaluate the prognostic value of MR-proANP in patients with HCM. Subjects and Methods: The present study was conducted at Narayana Medical College & Hospital, Chintareddy Palem, Nellore, Andhra Pradesh from July 2016 to July 2017 on 46 patients of hypertrophic cardiomyopathy of both genders. Serum NT-proBNP was measured by a two-site electrochemiluminescence immunoassay on a Roche Diagnostics E170 analyser. Results: The mean systolic blood pressure was 124.8 mm Hg, diastolic blood pressure was 78 mm Hg, heart rate was 68 beats/minutes, NYHA 1(n=4), NYHA 2 (n=27), NYHA 3–4 (n=15) and atrial fibrillation was 12%. The mean MR-proANP was 106 pmol/L and NT-proBNP was 540 pg/mL at the start of the study. At the end of 12 months of follow up, 15 patients had a primary end point defined as heart failure hospitalisation (n=10), heart transplant (n=3) death(n=2). Both mean MR-proANP and NT-proBNP were strongly associated with the primary end points at the end of study period with values of 1010 pmol/L and 2545 pg/ml respectively. This showed a strong association with P
Keywords: Heart Failure; Hypertrophic Cardiomyopathy; Immunoassay